Profiles and technological requirements of urogenital probiotics - Nader, Maria Elena Fatima (2015)
Probiotics, defined as live microorganisms that, when administered in adequate amounts, confer a health benefit on the host, are considered a valid and novel alternative for the prevention and treatment of female urogenital tract infections. Lactobacilli, the predominant microorganisms of the healthy human vaginal microbiome, can be included as active pharmaceutical ingredients in probiotics products. Several requirements must be considered or criteria fulfilled during the development of a probiotic product or formula for the female urogenital tract. This review deals with the main selection criteria for urogenital probiotic microorganisms: host specificity, potential beneficial properties, functional specifications, technological characteristics and clinical trials used to test their effect on certain physiological and pathological conditions. Further studies are required to complement the current knowledge and support the clinical applications of probiotics in the urogenital tract. This therapy will allow the restoration of the ecological equilibrium of the urogenital tract microbiome as well as the recovery of the sexual and reproductive health of women.